Antioxidant potential of different extracts and fractions of Catharanthus roseus shoots - Nasır Rasool,; Komal Rızwan,; Muhammad Zubaır,; Kaleem Ur Rahman Naveed,; Imran Imran,; Viqar uddin Ahmed, (International Journal of Phytomedicine, 2011)
Antioxidant effectiveness of indigenous medicinal plant C. roseus shoots extracts and fractions with solvents of different polarity (n–hexane, ethylacetate, methanol, chloroform) was assessed for total phenolics content (TPC), total flavonoid contents (TFC), DPPH radical scavenging activity and % inhibition of peroxidation in linoleic acid system. The C. roseus extracts and fractions contained appreciable levels of total phenolic contents 3.2 to 8.5 GAE (g/100g per dry matter) and total flavonoid contents 1.8 to 5.4 CE (g/100 of per dry matter). The C. roseus shoots extracts and fractions also exhibited good DPPH radical IC50, 28.2 to 119 µg/ml and Inhibition of Peroxidation in Linoleic Acid (38.4 to75.1%) respectively. Of the C. roseus shoots extracts and fractions tested, 100% methanolic extract exhibited the maximum antioxidant activity, the results of the present investigation demonstrated significant (p<0.05) variations in the antioxidant activity. The results of the present comprehensive analysis demonstrated that C. roseus extracts and fractions are a viable source of natural antioxidants and might be exploited for functional foods and nutraceutical applications.